Ann Brooks’ Postfeminist Studies on Omani Women’s Identity - Rasaf, Najma Imtinan; Basid, Abdul (Universitas Sanata Dharma, 2024)
This study aims to describe the aspects of influence and identity shaping of female characters in the novel